Neurodegenerative Diseases and Cholesterol: Seeing the Field Through the Players - Pfrieger, Frank W. (Frontiers in Aging Neuroscience, 2021)
Neurodegenerative diseases, namely Alzheimer's (AD), Parkinson's (PD) and Huntington's disease (HD) together with amyotrophic lateral sclerosis (ALS) and multiple sclerosis (MS), devastate millions of lives per year worldwide and impose an increasing socio-economic burden across nations. Consequently, these diseases occupy a considerable portion of biomedical research aiming to understand mechanisms of neurodegeneration and to develop efficient treatments. A potential culprit is cholesterol serving as essential component of cellular membranes, as cofactor of signaling pathways and as precursor for oxysterols and hormones. This article exposes the workforce studying research on neurodegeneration and cholesterol using the TeamTree analysis. This new bibliometric approach reveals the history and dynamics of the teams and exposes key players based on citation-independent metrics. The team-centered view reveals the players on an important field of biomedical research.